Efektivitas Metode Tilawati dalam Pembelajaran Al-Qur’an pada Siswa Kelas V di SDS (Swasta) Sekar Adi Cibinong Bogor - Izhar Syafawi Sya’ban; Sri Widyastri; Muh. Ubaidillah Alghifary Slamet (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study uses descriptive-qualitative research, the author uses field research which aims to describe and analyze the learning of the Qur'an using the tilawati method at SDS Sekar Adi. The data sources are in the form of primary sources through 5 informants including: the principal, head of curriculum, tilawati coordinator, tilawati teacher and fifth grade students obtained through observation, interviews and documentation as well as secondary data in the form of books, journals, laws and data obtained from the internet. The results of the learning evaluation at the location were that out of 44 fifth grade students who participated in the munaqosyah for increasing the juz level of the Al-Qur'an, 37 students were declared "passed" and 7 other students "improved", with a percentage of 84%. Students who did not pass, on average, made mistakes in the fields of fashohah and gharib musykilat, a special class was needed to discuss the material. The tilawati method is said to be effective for use as learning the Qur'an in that place because the learning process is already systematic and in collaboration with the Tilawati Center Jabar 1, the Qur'an teachers already have certificates and the Qur'an testimony so that students experience ease in learning to read the Qur'an, especially for grade V students.